2012
DOI: 10.1038/mt.2012.153
|View full text |Cite
|
Sign up to set email alerts
|

Extended Normal Life After AAVrh10-mediated Gene Therapy in the Mouse Model of Krabbe Disease

Abstract: Globoid cell leukodystrophy (GLD) or Krabbe disease is a neurodegenerative disorder caused by the deficiency of the lysosomal enzyme galactocerebrosidase (GALC). This deficiency results in accumulation of certain galactolipids including psychosine which is cytotoxic for myelin-producing cells. Treatment of human patients at this time is limited to hematopoietic stem cell transplantation (HSCT) that appears to slow the progression of the disease when performed in presymptomatic patients. In this study, adeno-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 46 publications
3
97
0
Order By: Relevance
“…Also the distribution, number and morphology of "globoid cells" seem to be very similar in humanized GALC mice and twitcher mice (compare Fig. 4A with twitcher histopathologies published in, e.g., Rafi et al, 2005Rafi et al, , 2012.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Also the distribution, number and morphology of "globoid cells" seem to be very similar in humanized GALC mice and twitcher mice (compare Fig. 4A with twitcher histopathologies published in, e.g., Rafi et al, 2005Rafi et al, , 2012.…”
Section: Discussionsupporting
confidence: 56%
“…The most effective so far have been adeno-associated virus (AAV)-mediated gene therapy using combined intracerebroventricular, intracerebellar, and intravenous injection of virus particles (Rafi et al, 2012), and a combination of bone marrow transplantation with AAV-mediated gene therapy , respectively. Both treatments were able to triple the 40 day-lifespan of untreated twitcher mice when administered to neonatal mice.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple injections-intracerebroventricularly, intracerebellarly, and intravenously-of AAVrh10-GALC was reported useful to optimize delivery and overall cross-correction: high enzyme activity was achieved in the brain and cerebellum, and moderate to high activity was detected in the spinal cord and the sciatic nerve of mice. Furthermore, treated newborn mice successfully lived up to 8 months despite the 40 days of untreated animals [21]. More recently, the same group demonstrated that mice receiving a single intravenous injection of AAVrh10-GALC at PND10 had no tremor and continued to gain weight until a few weeks before they died.…”
Section: Gene Technology In Therapymentioning
confidence: 99%
“…In recent studies, affected twitcher mice that received intracerebroventricular, intracerebellar, and intravenous injections of AAVrh10 vector had significant prolongation of their lives, robust GALC expression, improved myelination, retention of normal movement and, in some cases, restored ability of male and female mice to mate and rear their pups. 31 While the untreated twitcher mice live only about 40 days, many of the treated mice live for over 200 days. However, for some unknown reason after a relatively long period of apparent normalcy, the treated mice develop neurologic signs and die within a few weeks.…”
Section: Current Researchmentioning
confidence: 99%